2008
DOI: 10.1161/circulationaha.108.767673
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin-Like 1 Is an Akt-Regulated Cardioprotective Factor That Is Secreted by the Heart

Abstract: Background-The Akt protein kinase is an important mediator of cardiac myocyte growth and survival. To identify factors with novel therapeutic applications in cardiac diseases, we focused on the identification of factors secreted from Akt1-activated cells that have cardioprotective effects through autocrine/paracrine mechanisms. Methods and Results-Using an inducible Akt1 transgenic mouse model, we have found that follistatin-like 1 (Fstl1) protein and transcript expression are increased 4.0-and 2.0-fold, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
242
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(259 citation statements)
references
References 46 publications
(49 reference statements)
15
242
2
Order By: Relevance
“…In agreement with the current study, we recently reported that Fstl1 is up-regulated during cardiac hypertrophy (16). In this study, Fstl1 was shown to activate Akt signaling in cardiac myocytes and inhibit apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the current study, we recently reported that Fstl1 is up-regulated during cardiac hypertrophy (16). In this study, Fstl1 was shown to activate Akt signaling in cardiac myocytes and inhibit apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…HUVECs were infected with adenoviral constructs encoding mouse Fstl1 (Ad-Fstl1) (16), or Ad-␤-gal at a multiplicity of infection (m.o.i.) of 10 for 8 h and placed in endothelial cell basal medium-2 (Lonza) without serum for the indicated lengths of time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression is induced in the heart by ischaemic insults, and systemic administration of FSTL1 protects the heart from ischaemia/reperfusion injury [134]. Shimano et al have described cardiac FSTL1 as functioning as an auto-/paracrine regulatory factor that prevents myocyte hypertrophic growth and the loss of ventricular performance in response to pressure overload [133].…”
Section: Key Facts: Myokines As Therapeutic Targetsmentioning
confidence: 99%
“…13,14 Previously, we reported that Fstl1 is a cardiokine upregulated by various heart stresses, including cardiac ischemia/reperfusion injury, pressure overload, and myocardial infarction. 15,16 Cardiac myocytederived Fstl1 reduces pathologic cardiac hypertrophy induced by pressure overload. 16 Systemic administration of Fstl1 improves myocardial ischemia/reperfusion damage through reduction of myocyte apoptosis and inflammatory responses.…”
mentioning
confidence: 99%